1992
DOI: 10.1093/tropej/38.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Host Factors and Acute Lower Respiratory Infections in Pre-school Children

Abstract: The relationship between certain host-related variables and the short-term outcome of hospitalization for severe acute lower respiratory infections was studied prospectively in a cohort of 103 pre-school Nigerian children. The respective mean ages of those with bronchiolitis and croup were 3.2 months and 18.9 months while the corresponding M:F ratios were 2.5:1 and 1:1. It was highly significant that all the eight children that died were malnourished (P less than 0.01). Furthermore, malnourished subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…The majority of studies included a relatively small number of severely malnourished children with only five of the studies including more than 50 patients. Six studies used blood cultures alone to identify the causative organism (Berkowitz 1983; Friedland 1992; Johnson et al . 1992, 1993; Shimeles & Lulseged 1994; M.J. Chisti, unpublished data), four used lung aspirates alone (Hughes et al .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies included a relatively small number of severely malnourished children with only five of the studies including more than 50 patients. Six studies used blood cultures alone to identify the causative organism (Berkowitz 1983; Friedland 1992; Johnson et al . 1992, 1993; Shimeles & Lulseged 1994; M.J. Chisti, unpublished data), four used lung aspirates alone (Hughes et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the former, frequency, duration and severity have all been correlated with nutritional status in several prospective studies [6][7][8][9][10][11]. Undernutrition has also been shown to increase the severity of respiratory infections, particularly in younger children [12].…”
Section: Nutrition Disease and Survivalmentioning
confidence: 99%
“…Deivanayagam et al [10] and Nathoo et al [14] had found age under 6 month Johnson et al [15] interestingly, reported higher mortality in children above 12 months of age s to be significant.…”
Section: Discussionmentioning
confidence: 97%